Lichen Striatus Following The Pigmentary Demarcation Lines - Malakar Subrata; Lahiri Koushik; Malakar Rita Shah (Wolters Kluwer Medknow Publications, 2002)
Lichen striatus is an uncommon, self-limited, usually unilateral linear dermatosis of unknown aetiology. The lesions in two cases of lichen striatus, one on right cheek of a 7 year old boy for last 5 months and another on left arm of a 10 year old boy for last 3 months, exactly follow the pigmentary dermarcation lines: one, Pigmentary demarcation lines over the face (PDL-F) and the other Voigt-Futcher line (PDL-A). This observation might link between the linearity of lichen striatus and pigmentary demarcation lines.